Translation Policy in the Constitutional Courts of Western Europe: Authenticity vs. Authority - Kamal-Girard, Mathilde (Vertimo studijos, 2023)
This paper deals with the translation policy in the constitutional courts of Western Europe. These courts, which are set in unilingual systems, employ ‘disseminative translations’ as part of a mutual strategy of influence. More precisely, the aim of the article is to demonstrate a distortion between what a constitutional court intends to translate, what the court effectively translates, and how a counterpart court receives it in another legal system. The paper emphasizes the concept of translation authenticity in these courts and its consequences on normativity. Furthermore, it underlines that even with a lax conception of authenticity, these translations have a normative effect—albeit indirect.
Keywords: Legal translation; Constitutional Courts; Precedents; Legal sociology; Strategical analysis